Ubud’s Community Resilience in Facing the Covid-19 Pandemic - Pitanatri, Isvari Ayu; Putra, I Nyoman Darma; Yanthy, Putu Sucita (Jurnal Ekonomi Kuantitatif Terapan; 2023: Vol. 16, No. 1, Februari 2023 (pp.1-186), 2023)
The current Covid-19 pandemic has resulted the downfall of world tourism, including Bali. Ubud, which is one of the main stars of Bali tourism, is being severely affected by the pandemic situation because of the dependency of the Ubud community on the tourism sector. This study examines the resilience of the Ubud’s community in facing the Covid-19 pandemic which is influenced by community capital in the form of social capital, economic capital, cultural capital, institutional capital, and infrastructure capital. This community resilience then affects the community's decision in returning into the tourism sector in the post-pandemic situation. Quantitative research is conducted and the data was collected by distributing questionnaires to 100 respondents and supported by literature studies, observations, and interviews with informants related to this research. The results of the study found that social capital, economic capital, and cultural capital were in the good category and had a positive influence on the community resilience in Kawasan Wisata Ubud amid the Covid-19 pandemic.  That resilience increases the people's optimism about returning to the tourism sector in the post-pandemic situation.